Applicability of a Modified Rat Model of Acute Arthritis for Long-Term Testing of Drug Delivery Systems - Imke Rudnik-Jansen; Nina Woike; Suzanne de Jong; Sabine Versteeg; Marja Kik; Pieter Emans; George Mihov; Jens Thies; Niels Eijkelkamp; Marianna Tryfonidou; Laura Creemers (MDPI AG, 2019)
Episodes of inflammation and pain are predominant features of arthritic joint diseases. Drug delivery systems (DDS) could reduce inflammation and pain long-term without chances of infection upon multiple injections. To allow for long-term evaluation of DDS, we modified a previously published acute arthritis model by extending follow-up periods between flare-ups. Unilateral synovial inflammation of the knee was induced by intra-articular injection of streptococcal cell wall peptidoglycan polysaccharide (PGPS), and flare-ups were induced by intravenous PGPS injections every 4 weeks for a total duration of 84 days. In PGPS-reactivated animals, joint swelling, pain behavior, post mortem synovitis, and osteophyte formation were notable features. Hepatitis, splenitis and inflammation of non-primed joints were observed as systemic side effects. To test the applicability of the modified arthritis model for long-term testing of DDS, the duration of anti-inflammatory and analgesic effects of a corticosteroid released from two different polymer-based platforms was evaluated. The current modified arthritis model has good applicability for testing of DDS for a prolonged period of time. Furthermore, the novel autoregulatory polyesteramide (PEA) microsphere platform releasing triamcinolone acetonide (TAA) was benchmarked against poly lactic-co-glycolic acid (PLGA) and reduced joint swelling and pain behavior more potently compared to TAA-loaded PLGA microspheres.